2010
DOI: 10.1007/s00403-010-1089-5
|View full text |Cite
|
Sign up to set email alerts
|

Ficus deltoidea (Mas cotek) extract exerted anti-melanogenic activity by preventing tyrosinase activity in vitro and by suppressing tyrosinase gene expression in B16F1 melanoma cells

Abstract: Ficus deltoidea (Mas cotek) water extract has been widely used for woman health in Malaysia. Our investigation focused to identify anti-melanogenic efficacy of F. deltoidea since it has been known to have strong anti-oxidant activities. Anti-melanogenic effect of F. deltoidea extract was analyzed using cultured B16F1 melanoma cells. Cytotoxicity of the extract was measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and determined the highest concentration of the extract that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 37 publications
0
43
0
3
Order By: Relevance
“…Western blot is used in various studies which utilize expression profile of tyrosinase and other melanogenic enzymes to find out potent antimelanogenic agent. Oh et al [17] demonstrated reduced expression of tyrosinase and MITF gene by Ficus deltoidea extract through western blotting. Extracts of citrus press cakes, Oreocnide fruticosa and Agaricus bisporus were examined for their mealanogenic and antimelanogenic activity in terms of expression of melanogenic enzymes including tyrosinase by using western blot analysis [18][19][20].…”
Section: Different Assays Implemented For the Analysis Of Change In Tmentioning
confidence: 99%
“…Western blot is used in various studies which utilize expression profile of tyrosinase and other melanogenic enzymes to find out potent antimelanogenic agent. Oh et al [17] demonstrated reduced expression of tyrosinase and MITF gene by Ficus deltoidea extract through western blotting. Extracts of citrus press cakes, Oreocnide fruticosa and Agaricus bisporus were examined for their mealanogenic and antimelanogenic activity in terms of expression of melanogenic enzymes including tyrosinase by using western blot analysis [18][19][20].…”
Section: Different Assays Implemented For the Analysis Of Change In Tmentioning
confidence: 99%
“…In industrial point of view, cosmetics can help depigment skin color, which is one of the important parts among several functional cosmetic fields. Especially, development of novel whitening phytochemicals from natural sources has become new popular trends recently [10] . Actually, several studies have focused on the inhibition of melanogenesis and the prevention of abnormal pigmentation for cosmetic reasons [11][12][13] .…”
Section: P E E R R E V I E W Abstract Abstractmentioning
confidence: 99%
“…Cellular tyrosinase activity was measured by the method of Yen (1) rutin, (2) narirutin, (3) naringin, (4) hesperidin, (5) neohesperidin, (6) neohesperidin dihydrochalcone, (7) naringenin, (8) hesperetin, (9) aprgrnin, (10) nobiletin, (11) tangeretin, (12) auraptene was diluted with ethanol to obtain a series concentration of working solutions, and subjected to HPLC analysis.…”
Section: Determination Of Cellular Tyrosinase Activitymentioning
confidence: 99%
“…A secreted melanin assay was performed as described previously with slight modifications (34,35). After 48 h, the culture medium was harvested and centrifuged at 10,000 rpm for 10 min.…”
Section: 2-diphenyl-1-picrylhydrazyl (Dpph) Assaymentioning
confidence: 99%